Effects of exercise on lipid oxidation at rest: Comparison between high intensity interval exercise and endurance exercise - Chen, Raymond Senyuan (2016)
Background: Obesity and declining rates of exercise are often associated with many ailments including cardiovascular disease and atherosclerosis. although evidence indicate that both high intensity interval training (HIIT)and endurance training promote positive metabolic adaptations, however there has been significantly less research concerning the characteristics of an exercise bout that affect post exercise metabolism, particularly resting lipid oxidation. Aim: The main aim of the study was to examine the metabolic effects (resting lipid oxidation) of HIIT and endurance training Method: 8 recreationally active male subjects participated in a repeated measures study design consisted of 1 pre test session and 5 exercise training (ET) sessions of either HIIT or endurance training condition, and 1 post test session. Resting lipid oxidation rates of the subjects were taken from a ventilated hood set up. It was hypothesized that HIIT exercise training will have a greater positive effect on resting lipid oxidation than endurance training Result: Both HIIT and endurance training did not have a significant effect on resting lipid oxidation Conclusion: Although both HIIT and endurance training did not have a significant effect on resting lipid oxidation, there is literature, mostly longitudinal studies, which suggest that exercise do have significant metabolic changes. Thus longitudinal studies will be recommended for future studies.